PERBEDAAN SUHU DESTILASI TERHADAP MUTU DAN AKTIVITAS ANTIBAKTERI ASAP CAIR DARI SABUT KELAPA MUDA - Andesmar Andesmar; Raswen Efendi; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to obtain optimum liquid smoke from young coconut fibers with different destillation temperature treatments, and meet SNI number 01-2725-2009. This research was conducted using a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications to obtain 16 experimental units. The data obtained were statistically analyzed using ANOVA, if F is greater than or equal to F table, then continued with DNMRT test at the 5% level. The results of each treatment showed significant differences in each treatment from pH, and acid levels, but did not have a significant effect on antibacterial activity. The best selected treatments in this study were distillation temperatures of 200°C with a pH of 2.52, acid levels of 1.158%, composition (% area) phenol of 64.06%, antibacterial against Eschericia coli 7.60 mm, and antibacterial against Staphylococcus aureus 13.57 mm. Key words: young coconut fiber, destilation, liquid smoke